(untitled) (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
The documentary film entitled The Malayan Emergency (2010) was the documentary film that highlights the importance of unity in the formation of the Malaysian nation. This documentary film production has become an important platform for the Malaysian Government to promote the 1Malaysia initiative launched by a former, the 6th Malaysian Prime Minister, Najib Tun Razak in 2009. Thus, the broadcast of this documentary film is very important in order for the message in the documentary film to better, and more accurately, reach the target audience. The historical representation in the form of audio and visual is seen to be a more effective broadcast and story-telling to understand history. The aim of this study is to carry out an analysis from the aspect of aesthetics media towards the documentary film The Malayan Emergency (2010) seen to be an official version about the history of the Malayan Emergency and the important platform in promoting the 1Malaysia initiative. The study outcome shows that the aesthetics media used in the documentary film The Malayan Emergency (2010) has constructed the meaning in line with the ideology that is to be conveyed to the target audience. The goal of the aesthetics media in this film is to make it more realistic and to add to the dramatic impact to the documentary film visual.